Prospects for the Development of Green Business in the Agro-Industrial Complex - BOLATBEK, Botagoz; SALIMBAYEVA, Rassima; SATBAEVA, Gulbarshyn; SAPARALIYEVA, Kulshat; USSUBALIYEVA, Saltanat (Journal of Environmental Management and Tourism, 2019)
The article analyses the various theoretical approaches to the planning of agricultural and food areas of Kazakhstan. The author considers that the method of forecast scenarios in development of green business as the most effective one. Kazakhstan has all the prerequisites to produce a wide range of food products in volumes that ensure not only the country's food security, but also the opportunity to expand export performance in world markets. At the same time, the available food potential is not being used effectively. This is evidenced, first, by the irrational structure of imports of food products, many of which could be produced at domestic enterprises. In these conditions, it is necessary to search for the most appropriate scientific approaches to the organization of strategic management of the agro-food sector by improving the analysis, planning and forecasting of its development trends, considering the influence of various factors.